Key barriers to the effective development of innovation activities of small and medium business in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Successful implementation of innovative processes depends largely on the internal potential of innovative organizations. This dependence is widely studied, both in domestic and foreign literature. Lack of sufficient innovative potential of reducing the effective implementation of innova-tion. In this article, the author puts forward the following hypotheses: Ka-zakhstan organization of small and medium-sized businesses do not have sufficient domestic innovative capacity; Inadequate internal innovation capability is a major obstacle to the effective implementation of innovative processes Kazakh small and medium enterprises (SMEs).The purpose of this article is to conduct empirical analysis conducted by the author in 2012-2014, (to verify the above hypotheses), and on this basis to determine the main barriers to effective implementation of innova-tion. innovative development of Kazakhstan, barriers, small and medium businesses.
Keywords: innovative development of Kazakhstan; barriers; small and medium businesses.